1995
DOI: 10.1063/1.115268
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of aluminum films deposited on sputtered-titanium nitride/silicon substrate by metalorganic chemical vapor deposition from dimethylethylamine alane

Abstract: Al films deposited on sputtered-TiN/Si substrate by metalorganic chemical vapor deposition (MOCVD) from dimethylethylamine alane (DMEAA) were characterized using x-ray diffraction (XRD), Auger electron spectroscopy (AES), atomic force microscopy (AFM), and transmission electron microscopy (TEM). The TiN film sputtered on the Si has a preferred orientation along the growth direction with the 〈111〉 of the film parallel to the Si〈111〉. Sputtering of the TiN film on the Si induced strains at the interface. The TiN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…4,5 Kaizuka et al and Li et al reported that Al films on CVD-TiN͑111͒ films showed ͑111͒ preferred orientation. [6][7][8] Study of the microstructure and surface roughness of copper films deposited on crystallized metallorganic ͑MO͒CVD-TiN substrates was reported. 9 Gittis and Dobrev explained preferred orientation in the film in terms of the surface energy and kinetic factors.…”
mentioning
confidence: 99%
“…4,5 Kaizuka et al and Li et al reported that Al films on CVD-TiN͑111͒ films showed ͑111͒ preferred orientation. [6][7][8] Study of the microstructure and surface roughness of copper films deposited on crystallized metallorganic ͑MO͒CVD-TiN substrates was reported. 9 Gittis and Dobrev explained preferred orientation in the film in terms of the surface energy and kinetic factors.…”
mentioning
confidence: 99%
“…In Fig. 9(a), the 2θ peak appeared at 38.52, 45.10, and 65.14 degrees with the orientation of 111, 200, and 220 respectively corresponding to Al crystal peaks (JCPDS number: 00-004-0787) [21], [29].…”
Section: E Surface Morphology and Structural Characterizationmentioning
confidence: 99%
“…On the other hand, the scratched tester is used in the case of dry coating for example titanium nitride (TiN). [2][3][4][5][6][7][8][9] In the experiment on the plating are never seen.…”
Section: Introductionmentioning
confidence: 99%